Navigating the Challenges of Ureteral Stones: A Comparative Analysis of Outcomes for Impacted and Non-Impacted Stones Treated with Semi-Rigid Ureteroscop - Khan, Maaz; Majeed, Zahid; Rahman, Misbah Ur; Sohail, Nadeem; Khan, Nasir (Biological and Clinical Sciences Research Journal, 2025)
Impacted ureteral stones pose significant clinical challenges and are associated with higher complication rates and increased operative difficulty. In developing countries like Pakistan, delayed diagnosis often leads to stone impaction. This study aimed to compare the intraoperative and postoperative outcomes of impacted versus non-impacted ureteral stones managed with semi-rigid ureteroscopy in a tertiary care setting. Methods: A prospective comparative study was conducted at the Institute of Kidney Diseases, Peshawar, from April to September 2024. Seventy-six patients with solitary ureteral stones were enrolled and classified intraoperatively into impacted and non-impacted groups. All patients underwent semi-rigid ureteroscopy with pneumatic lithotripsy. Data collected included demographics, stone size, operative time, complications, hospital stay, and stone-free rates (SFR). Statistical analysis was performed using SPSS v26, with p-values of less than 0.05 considered statistically significant. Results: The impacted group had significantly larger stones (mean size, 10.2 mm vs. 8.5 mm; p < 0.01) and longer symptom durations (7.8 vs. 3.1 weeks; p < 0.001). Operative time was longer (42.5 vs. 30.7 minutes; p<0.001), and ureteral dilation was more frequently required (71.1% vs. 23.7%; p<0.001) in the impacted group. Intraoperative bleeding (15.8% vs. 2.6%; p=0.04) and postoperative pain (52.6% vs. 26.3%; p=0.02) were significantly higher in impacted stones. A prolonged hospital stay (more than 24 hours) was observed in 47.4% of impacted cases, compared to 21.1% in non-impacted cases (p = 0.01). SFR was comparable between groups (89.5% vs. 97.4%; p = 0.18). Stone impaction and prolonged operative time were independent predictors of extended hospital stay. Conclusion: Impacted ureteral stones are associated with increased operative complexity, higher complication rates, and prolonged hospitalisation, despite similar stone clearance rates to non-impacted stones. Early detection and timely intervention are crucial for enhancing patient outcomes in resource-constrained settings.